CHROME VI REMOVAL FROM SYNTHETIC WATER LEVEL LABORATORY, USING LAYERED DOUBLE HYDROXIDES (HDL) - Murgueitio, Erika (2015)
Four types of double layered hydroxides (HDL) were synthesized with Al / Mg molar ratioof 4:1, using analytical and technical grade reagents. Batch essays were conducted in whichit was determined that the adsorption capacity of chromium VI is proportional to the initialconcentration, to the four adsorbents (α = 0,05; F> F critical). It was also determined that itis viable the use of lower cost technical grade reagents for the synthesis, since the adsorbentshave similar level of efficiency, both with sintetic water (distilled water with competing ions:80 ppm HCO3-, 100 ppm Cl-, 120 ppm SO4= and different concentrations of Cr VI) andindustrial water. In batch equilibrium tests with synthetic water it was established a 54% ofadsorption; with industrial water about 19% was obtained, both at 120 minutes. The isothermmodel that fits the adsorption behavior is Freundlich which indicates a multilayer adsorption.Adsorption kinetics is consistent with the pseudo-first order model, which is a physicaladsorption and ion exchange. In a fixed bed column with synthetic water 70% removal of chromium VI was achieved. When industrial water was treated the removal reached to98.4% and thus the values remained below the permissible limit for discharge to drain. Theusing of HDL in a fixed bed column at pH 2,8 significantly decreases chromium VI fromthe effluent in chrome industry appliances. Is recommended the Use of HDL to treat highlypolluted effluents and to transfer them to a solid matrix, easily manageable for environmentalmanagers.